Synthesis and Characterization of Copper Sulfide‐Manganese Sulfide Nanoparticles with Chestnut Morphology and Study on the Semiconducting Properties. Issue 13 (4th April 2019) - Gupta, Kanika; Singh, Maninder; Mohan, Priyank; Mott, Derrick; Maenosono, Shinya
Abstract: Heterostructured nanoparticles composed of copper sulfide and manganese sulfide were synthesized by using a bottom up, wet‐chemical approach. This thermolysis based technique leads to chestnut shapes with a complex structure which is elucidated by using scanning transmission electron microscopy and elemental mapping. The particles semiconducting properties were then studied including electrical conductivity, thermal conductivity and Seebeck coefficient. The results reveal insight and challenges in the design and implementation of heterostructured chalcogenide type nanoparticles for semiconducting applications. Abstract : Copper sulfide – manganese sulfide nanoparticles have potential applications in a wide variety of semiconductors because of their potentially tunable properties. Copper sulfide possesses unique electrical conductivity properties while manganese sulfide has an exceptionally high Seebeck coefficient. These two materials were combined into a single heterostructured nanoparticle to probe the resulting semiconducting characteristics.